Designed formation of double‐shelled ni–fe layered‐double‐hydroxide nanocages for efficient oxygen evolution reaction - Zhang, Jintao (2020)
Delicate design of nanostructures for oxygen‐evolution electrocatalysts is an important strategy for accelerating the reaction kinetics of water splitting. In this work, Ni–Fe layered‐double‐hydroxide (LDH) nanocages with tunable shells are synthesized via a facile one‐pot self‐templating method. The number of shells can be precisely controlled by regulating the template etching at the interface. Benefiting from the double‐shelled structure with large electroactive surface area and optimized chemical composition, the hierarchical Ni–Fe LDH nanocages exhibit appealing electrocatalytic activity for the oxygen evolution reaction in alkaline electrolyte. Particularly, double‐shelled Ni–Fe LDH nanocages can achieve a current density of 20 mA cm−2 at a low overpotential of 246 mV with excellent stability.